Injury Tracker - Sport Injury Management Software
Injury Tracker is a complete Windows 95/NT solution for managing all aspects of athlete health - from injury tracking and reporting, to charting and documentation of treatments, visits, tests, prescriptions, surgeries and more. IT is ideal for busy athletic trainers, team physicians or other medical professionals interested in a better method of managing athlete health records - especially within a networked environment. IT is also an extremely powerful research tool for users in need of in-depth statistical analysis of injury distributions and trends.